Dunkirk [videorecording (DVD)] - Nolan, Christopher, 1970-; Whitehead, Fionn, 1997-; Bonnard, Damien, 1978-; Barnard, Aneurin, 1987- (Warner Bros. Home Entertainment, 2017)
A World War II thriller about the evacuation of Allied troops from the French city of Dunkirk before Nazi forces can take hold.